Infrared Drying of Natural and Cultivated Asparagus: Effect of Energy Input on the Drying Characteristics and Physicochemical Quality - Kocabay, Ozlem Gokce; Ismail, Osman (SELCUK UNIV PRESS, 2026)
The aim of this study is to investigate the drying kinetics of asparagus using the infrared drying method for the first time. In the present study, drying characteristics of both natural and cultivated asparagus samples were examined at 104, 125, 167, and 209 W power levels. The drying times for natural asparagus samples were found to be 90, 75, 60, and 45 minutes at 104, 125, 167, and 209 W, respectively. In contrast, the corresponding drying times for cultivated asparagus samples were 120, 105, 90, and 75 minutes at the same power levels. According to the statistical parameter calculations, the R2, RMSE and chi 2 values for natural asparagus samples ranged from 0.9938 to 0.9995, 0.000062 to 0.000779, and 0.007128 to 0.023547, respectively. For cultivated asparagus samples, these values ranged from 0.9919 and 0.9999, 0.000016 and 0.001343 and 0.000738, and 0.027984, respectively. For both products, the effective moisture diffusivity values increased with increasing infrared power. The Deff values for natural asparagus samples were calculated as 7.02 x 10-10, 1.19 x 10-9, 1.53 x 10-9, and 1.90 x 10-9 m2 s-1 at 104, 125, 167, and 209 W, respectively. However, the Deffvalues for cultivated asparagus samples were found to be 4.28 x 10-9, 4.84 x 10-9, 6.16 x 10-9, and 7.35 x 10-9 m2 s-1 at 104, 125, 167, and 209 W, respectively. High L* and low a*/b* values were obtained at an infrared power level of 104 W for both asparagus samples. The Aghbashlo et al. model was identified as the optimal model for describing the drying behavior of asparagus samples. According to the results of the color analysis, the best dried product quality was obtained at the 104 W power level for both natural and cultivated asparagus samples.
Keywords: Asparagus; Color characteristics; Effective moisture diffusivity; Infrared power; Kinetic models; Thin-layer drying; KINETICS; COLOR; CONSUMPTION; L.; Agriculture